Daya Hambat Ekstrak Daun Sirsak, Kirinyuh, dan Rimpang Lengkuas terhadap Pertumbuhan Koloni Colletotrichum acutatum - Ida Hodiyah; Elya Hartini; Amir Amilin; Moch Fauzian Yusup (Jurusan Agroteknologi, 2017)
Several plants that are potentially used as bio-pesticides are soursop, siam weed, and galangal. The research objective was to find out the effectiveness of leaf extract of soursop and C. odorata, and extract of galangal rhizome in inhibiting the growth of Colletotrichum acutatum colonies, causing antracnose on chilli, in in vitro. The experiment was conducted in the laboratory of Agriculture Faculty, Universitas Siliwangi Tasikmalaya from July until August 2016. The research design used was a completely randomized design consisted of nine treatments and three replications. The treatments were A ( control); B (soursop leaf extract, 0,5%); C (soursop leaf extract, 1%); D (C. odorata leaf extract, 0,5 %); E (C. odorata leaf extract 1%); F (galangal rhizome extract 0,5%); G (galangal rhizome extract 1%); H (mixture of soursop leaf extract, C. odorata leaf extract, and galangal rhizome extract each 0,5%; and I (mixture of soursop leaf extract, C. odorata leaf extract, and galangal rhizome extract each 1%). The results showed that the mixture of each 1% soursop leaf extract, C.odorata leaf extract and galangal rhizome extract was effective in inhibiting the growth of C. acutatum colonies at 7 and 14 days incubation period by 66,19% and 69,94% respectively. The three extracts are potentials as anti-fungus of C. acutatum.